Issues Of Enlightenment And The Education Of A Complete Generation In The Activities Of Jadids - Erkayeva Munira Aliyevna (Genius Journals, 2024)
The article discusses the issues of enlightenment and the upbringing of a mature generation in the activities of modernists. Enlightenment and generation upbringing are considered very important topics for the activities of modernists nowadays. The main principles of modernist upbringing, various enlightenment models, the specialization of the generation, and its significance are widely demonstrated in this topic. When the content and substance of the subject are considered, the issues of enlightenment and generation upbringing in modernist activities are analyzed extensively and deeply.
Keywords: enlightenment; modernist activity; upbringing of a mature generation